An updated checklist of the phlebotomine sand flies of Veracruz, Mexico (Diptera: Psychodidae, Phlebotominae) - Ibáñez-Bernal, Sergio; Suárez-Landa, Teresa; Mendoza, Fredy (Zootaxa, 2011)
Previous records of phlebotomine sand flies from Mexico included 14 species in the state of Veracruz. In this work, new records of some species are given, including four species not previously known to occur in Veracruz and one previously unknown from Mexico. 18 species of Phlebotominae are now known to occur in Veracruz.